2016
DOI: 10.5815/ijmecs.2016.08.06
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Mobile Devices for Learning in Higher Education Institutions: Nigerian Universities Case Study

Abstract: Abstract-Mobile devices such as smartphones and tablets are becoming increasing popular among students, setting out a new way to communicate, collaborate and learn. The use of portable devices has the capability to inspire new approaches to learning. It is therefore important to examine the students" viewpoints about the educational use of mobile technology in supporting the learning process. The purpose of this study is to determine the impact of mobile devices for learning purposes by exploring the kinds of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 18 publications
5
28
1
Order By: Relevance
“…These results were consistent with other studies that have shown that the application of mobile learning interventions could improve students' learning performance (Chu et al, 2010;Liu et al, 2009). Our study is slightly different in focus from previous work, for example in Bidin and Ziden (2013), Isiaka et al (2011), Liu et al (2012, Ozdamli and Uzunboylu (2015), Shonola et al (2016), andSung et al (2016), which predominantly explored mobile learning from different perspectives, such as adoption and application, feasibility studies of mobile learning implementation, split-attention and redundancy effects in mobile learning, prospects and challenges of mobile learning, adequacy and perceptions of m-learning, the impact of m-learning, and the meta-analysis of effects of mobile learning integration on learning performance. While these reports are interesting, our findings support an extension of novelty about the improvement of learning achievement with a mobile learning tool.…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…These results were consistent with other studies that have shown that the application of mobile learning interventions could improve students' learning performance (Chu et al, 2010;Liu et al, 2009). Our study is slightly different in focus from previous work, for example in Bidin and Ziden (2013), Isiaka et al (2011), Liu et al (2012, Ozdamli and Uzunboylu (2015), Shonola et al (2016), andSung et al (2016), which predominantly explored mobile learning from different perspectives, such as adoption and application, feasibility studies of mobile learning implementation, split-attention and redundancy effects in mobile learning, prospects and challenges of mobile learning, adequacy and perceptions of m-learning, the impact of m-learning, and the meta-analysis of effects of mobile learning integration on learning performance. While these reports are interesting, our findings support an extension of novelty about the improvement of learning achievement with a mobile learning tool.…”
Section: Discussioncontrasting
confidence: 85%
“…Velghe (2013) argued that the acceptance of the mobile phone in Africa has increased interest in literacy and introduced new opportunities to societies' deprived, marginalized, and less privileged. Technological innovations and contextualized learning opportunities offered by mobile learning are attractive and exciting to learners (Shonola et al, 2016). In the words of Kafyulilo (2014), "… mobile phones are considered as vital tools for both teaching and learning processes that can best serve as alterna tive device for overcoming the shortage of technological tools in schools in Tanzania and enhance students' learning from anywhere and at any time" (p. 2).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Although mobile device ownership could form a basis for comparison, usage of these devices for m-learning is an important factor to be considered. As noble as the previous studies are, the studies have not been able to consider the learners' experiences with m-learning and those factors that influence adoption of m-learning in Nigeria [2], [3], [4], [5] and [6].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Shonola (2016) has shared a position regarding the use of those devices in the International Education Industry. Since the scope of the business is the learning market, smart devices have the ability of inspiring new approaches to learn.…”
Section: Web/mobile Marketingmentioning
confidence: 99%